Beyond Cations: Expanding the Horizons of Ferrocene-Based Electrochemical Sensors for Neutral and Anionic Molecules - Angel A. J. Torriero; Alma M. Torriero; Kiara T. Miller; Ashwin K. V. Mruthunjaya (Inorganics)
Ferrocene (Fc) has long been celebrated for its remarkable redox properties and structural versatility, making it a cornerstone of electrochemical sensor development. While extensive research has focused on cation detection using Fc-based systems, the equally critical recognition of neutral and anionic molecules remains underexplored despite their significance in biological, environmental, and industrial contexts. This review addresses this gap by exploring the latest advancements in Fc-based electrochemical sensors designed to overcome the unique challenges posed by these species—including diverse geometries, high hydration enthalpies, and the absence of formal charge. Molecular architectures such as amide-functionalised receptors, urea derivatives, Lewis acid-containing receptors, triazolium, and carboxylic acid-containing systems are examined, highlighting how these sensors achieve high selectivity and sensitivity. Furthermore, the influence of solvent environments on sensor performance is discussed, providing a critical analysis of how different receptor functionalities and solvents affect sensor behaviour. Emphasising the advantages of redox-based detection, this review aims to inspire further innovation in developing Fc-based technologies for detecting neutral and anionic species.